Instruments in Identifying Representational Competence in Chemistry: A Systematic Literature Review - Rosyida, Ima; Rahayu, Sri; Dasna, I Wayan (Jurnal Pendidikan MIPA, 2022)
This literature review research aims to determine the instrument test in identifying representational competence in chemistry. The identified abilities involve how students can use, interpret, translate, and connect multiple representations to improve representation competence. The method used in this present study is SLR method by using meta-analysis approach by comparing information in some research literature study from 2011-2021 in the ERIC database, google scholar, and SINTA. Based on the results of research on 7 reviewed articles, it showed that several open-ended questions (57.14%) and multiple-choice instruments (57.14%) are the most widely used instruments to identify students' representational competence. The findings of the research show that there are several instruments that are combined with other instruments to strengthen the analytical method in obtaining data and completing the shortcomings of other instruments. In addition, there are several instruments made by aspects to measure how far the students' representational competence are. The information obtained from the use of the instrument can be used to determine the development of students' abilities in understanding chemistry using representations.Keywords: representational competence in chemistry, instrument test, literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1099-1111